Capturing the Long-Sought Dy@IC2v/I-C[sub.80] via Benzyl Radical Stabilization - Han, Xinyi; Xin, Jinpeng; Yao, Yangrong; Liang, Zhihui; Qiu, Yongfu; Chen, Muqing; Yang, Shangfeng (Nanomaterials (Basel, Switzerland), 2022)
Endohedral metallofullerenes (EMFs) are one type of intriguing metal/carbon hybrid molecule with the molecule configuration of sphere cavity-encapsulating metal ions/metal clusters due to their unique physicochemical properties and corresponding application in the fields of biological materials, single molecule magnet materials and energy conversion materials. Although the EMF family is growing, and versatile EMFs have been successfully synthesized and confirmed using crystal structures, some expected EMF members have not been observed using the conventional fullerene separation and purify strategy. These missing EMFs raise an interesting scientific issue as to whether this is due to the difficulty in separating them from the in situ formed carbon soot. Herein, we successfully captured a long-sought dysprosium-based EMF bearing a C2v(5)-C[sub.80] cage (Dy@C2v(5)-C[sub.80] ) in the form of Dy@C2v(5)-C[sub.80] (CH[sub.2] Ph)(Ph = −C[sub.6] H[sub.5] ) from carbon soot containing versatile EMFs using simple benzyl radical functionalization and unambiguously confirmed the molecule structure using single crystal X-ray diffraction characterization. Meanwhile, the crystal structure of Dy@C2v(5)-C[sub.80] (CH[sub.2] Ph) showed that a single benzyl group was grafted onto the (5,6,6)-carbon, suggesting the open-shell electronic configuration of Dy@C2v(5)-C[sub.80] . The theoretical calculations unveiled that the benzyl radical addition enables the modulation of the electronic configuration of Dy@C2v(5)-C[sub.80] and the corresponding stabilization of Dy@C2v(5)-C[sub.80] in conventional organic solvents. This facile stabilization strategy via benzyl radical addition exhibits the considerable capability to capture these missing EMFs, with the benefit of enriching the endohedral fullerene family.